Transcriptional signature of human pro-inflammatory TH17 cells identifies reduced IL10 gene expression in multiple sclerosis. Issue 1 (December 2017) - Hu, Dan; Notarbartolo, Samuele; Croonenborghs, Tom; Patel, Bonny; Cialic, Ron; Yang, Tun-Hsiang; Aschenbrenner, Dominik; Andersson, Karin; Gattorno, Marco; Pham, Minh; Kivisakk, Pia; Pierre, Isabelle; et al.
Abstract We have previously reported the molecular signature of murine pathogenic TH 17 cells that induce experimental autoimmune encephalomyelitis (EAE) in animals. Here we show that human peripheral blood IFN-γ+ IL-17+ (TH 1/17) and IFN-γ− IL-17+ (TH 17) CD4+ T cells display distinct transcriptional profiles in high-throughput transcription analyses. Compared to TH 17 cells, TH 1/17 cells have gene signatures with marked similarity to mouse pathogenic TH 17 cells. Assessing 15 representative signature genes in patients with multiple sclerosis, we find that TH 1/17 cells have elevated expression ofCXCR3 and reduced expression ofIFNG, CCL3, CLL4, GZMB, andIL10 compared to healthy controls. Moreover, higher expression ofIL10 in TH 17 cells is found in clinically stable vs. active patients. Our results define the molecular signature of human pro-inflammatory TH 17 cells, which can be used to both identify pathogenic TH 17 cells and to measure the effect of treatment on TH 17 cells in human autoimmune diseases. CD4+ T cells secreting interleukin-17 (TH 17) have diverse functions in modulating autoimmune diseases. Here the authors show via transcriptome analyses that a subset of human TH 17 co-expressing interferon-γ (TH 1/17) has a molecular signature similar to "pathogenic" mouse TH 17 but distinct from "non-pathogenic" mouse TH 17.